Metabolic Desynchronization in Critical Conditions: Experimental Study - G. V. Livanov; M. V. Aleksandrov; S. A. Vasilyev; Kh. V. Batotsyrenova; B. V. Batotsyrenov; A. N. Lodyagin; M. A. Lutsyk; A. V. Nosov (Общая реаниматология, 2006)
Objective. To conduct an experimental study of the impact of the time of administration of succinic acid preparations on central nervous system (CNS) function and gas exchange while simulating metabolic therapy for severe poisoning by ethyl alcohol. The study was performed on 74 male albino rats weighing 140—180 g. Acute severe and very severe intoxication was simulated, by intraabdominally administering 30% ethanol to the rats. Cytoflavin was used to simulate experimental therapy. The rate of gas exchange was estimated by the oxygen uptake determined by the closed chamber method in a Regnault apparatus (Germany). Spontaneous bioelectrical activity was recorded in the frontooccipital lead by the routine procedure. External pain stimulation and rhythmical photostimulation were employed to evaluate cerebral responsiveness. Heterodirectional EEG changes in the «early» and «late» administration of succinate were not followed by the similar alterations of gas exchange: oxygen consumption in both the «early» and «late» administration of succinate remained significantly lower than in the control animals. With the late administration of succinate to the animals with mixed (toxic and hypoxic) coma, the so-called discrepancy between the noticeably increased energy production and brutally diminished metabolism occurred. It may be just the pathological mechanism that was the basis for higher mortality in the late succinate administration group. The findings and their analysis make it possible to advance a hypothesis that succinate may cause metabolic desynchronization if activation of metabolic processes takes place under severe tissue respiratory tissue depression. In these cases, there is a severe damage to tissue and chiefly the brain. This manifests itself as EEG epileptiform activity splashes preceding the animals’ death. Therefore, resuscitation aimed at restoring the transport of oxygen and its involvement in tissue energy processes should be followed by the administration of succinic acid preparations. The drug of this kind is now perfluorane, as demonstrated by experimental and clinical studies. It should be noted that the more potent a metabolic agent is, the more strictly the rules of its use should be observed.